Distributed anonymous authentication scheme based on the blockchain in VANET - Xia FENG; Kaiping CUI; Qingqing XIE; Liangmin WANG (Tongxin xuebao)
Identity authentication is the first line of defense against malicious vehicles spreading false traffic information.However, due to the limited network bandwidth and computing power in the vehicle ad-hoc network (VANET), the existing schemes cannot meet the requirements of efficient authentication, nor can achieve fast and anonymous traceability of malicious vehicles.In view of this, a distributed anonymous authentication scheme based on the blockchain was proposed.The zero-knowledge proof was used to quickly and anonymously authenticate the identity of vehicles in VANET, and the pairing-free-based aggregating signature was used to provide fast batch verification, effectively reducing the computational burden generated during the authentication process.In addition, the regional trusted authority (RTA) could realize the anonymous traceability of malicious vehicle identities, and quickly revoke their identities by using the block chain.It could also update the short-term anonymous identities of vehicles based on local keys in time to ensure that vehicles anonymity and freshness of signatures.Security analysis and simulation show that the proposed scheme can satisfy various security requirements such as anonymity and unlinkability, and can effectively reduce computing and communication overhead, which is at least 27.28% higher in performance than similar schemes.